Erwiderung auf die Replik von Christian Hecker - Carl Christian von Weizsäcker (Wirtschaftsdienst, 2013)
Im Sonderheft 2013 'Verdient der Markt noch unser Vertrauen?' veröffentlichte der Wirtschaftsdienst einen Aufsatz von Carl Christian von Weizsäcker mit dem Titel 'Der Vorsorge-Albtraum'. Dazu äußert sich Christian Hecker kritisch. Anschließend stellt Carl Christian von Weizsäcker in einer Erwiderung seine Sicht dar. – – Weizsäcker suggests that maintenance or even an increase in the current level of government debt is necessary to provide people with opportunities to save for the future. However, there are several politico-economic reasons for a reduction of public debt. Moreover, if people start to doubt the sustainability of an increasing percentage of public debt, a vicious circle can lead to a debt crisis, which would threaten the country's political and economic stability. Public debt is not a burden for later generations when the rate of interest is below the rate of growth. Public debt may cause problems for the economy, but the absence of public debt also causes problems. Germany raised substantial implicit public debt by providing guarantees for the public debt of other euro countries, but if Germany had let the euro collapse, the 'new Deutsche Mark' would have caused a severe deflation, which also would have led to increased public debt. The new era of the 'provision nightmare' requires a 'new thinking' concerning public debt. Whenever the capital market adopts this new thinking, it will develop instruments to stabilise the economy even at high levels of public debt.
Keywords: H6; 330